2017
DOI: 10.1186/s40200-017-0287-5
|View full text |Cite
|
Sign up to set email alerts
|

Salivary glucose in monitoring glycaemia in patients with type 1 diabetes mellitus: a systematic review

Abstract: BackgroundIncidence of type 1 diabetes mellitus is increasing worldwide. Monitoring glycaemia is essential for control of diabetes mellitus. Conventional blood-based measurement of glucose requires venepuncture or needle prick, which is not free from pain and risk of infection. The non-invasiveness, ease and low-cost in collection made saliva an attractive alternative sample. The objective of this review was to systematically review the evidence on the relationship between salivary glucose level and blood gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…While the exemplary analysis of glucose in saliva herein has been selected as an example demonstrating the device performance for analysis in a complex real-world matrix, further research on improved evaluation algorithms and with an increased number of patients has to be executed for evaluating the potential relationship between blood and glucose levels. 37 For a more precise and accurate quantitative evaluation of salivary glucose levels, the complexity of the molecular composition of saliva requires applying advanced multivariate calibration algorithms during further studies to adequately represent potentially interfering molecules such as glycated proteins, inorganic salts, etc.…”
Section: Analysis Of Human Salivamentioning
confidence: 99%
“…While the exemplary analysis of glucose in saliva herein has been selected as an example demonstrating the device performance for analysis in a complex real-world matrix, further research on improved evaluation algorithms and with an increased number of patients has to be executed for evaluating the potential relationship between blood and glucose levels. 37 For a more precise and accurate quantitative evaluation of salivary glucose levels, the complexity of the molecular composition of saliva requires applying advanced multivariate calibration algorithms during further studies to adequately represent potentially interfering molecules such as glycated proteins, inorganic salts, etc.…”
Section: Analysis Of Human Salivamentioning
confidence: 99%
“…Currently, a broad set of methods are used to analyze saliva including immunoassays, colorimetric, enzymatic, kinetic, chromatographic and mass spectrometric analysis [11]. Several studies showed higher salivary glucose levels in DM patients than non-hyperglycemic controls, however, the studies reject the idea of a direct relationship between salivary glucose and glycemia in diabetic patients [6,[12][13][14][15][16][17]. Another limitation of salivary-based measurement of glucose for diabetes monitoring is the presence of glucose in foods, which can disturb the monitoring process as it induces changes in salivary glucose concentration.…”
Section: Introductionmentioning
confidence: 99%
“…3d, inset). [35][36][37][38] To evaluate the ability of the sensor to detect glucose in saliva, we collected a saliva sample from a healthy, non-diabetic volunteer who was asked to fast 12 h before the extraction of saliva. Using a commercially available glucose assay kit, we found glucose in this sample at a concentration of 28 µM.…”
Section: Resultsmentioning
confidence: 99%
“…4b). [35][36][37][38] Diabetic patients are advised to keep their blood glucose levels close to the target range below 7 mM (fasting). 39,40 Recent studies have demonstrated a significant positive correlation between the concentration of glucose in saliva and blood for healthy and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation